Roles of English for specific purposes (ESP) in STEM education to leverage sustainable education / Karmila Rafiqah M. Rafiq, Harwati Hashim and Melor Md Yunus - M. Rafiq, Karmila Rafiqah; Hashim, Harwati; Md Yunus, Melor (Universiti Teknologi MARA, 2024)
The rise of technology in education has opened up more career opportunities in the Science, Technology, Engineering, and Mathematics (STEM) fields. However, one factor which causes the decline in STEM pursuers in higher education is the language barrier. This is because the English language learnt in school is not specified for the STEM field, so the term English for Specific Purposes (ESP) comes into view. This paper aims to discuss the roles of ESP in relation to STEM education in Malaysia. The major theme revolves around language issues in STEM education, the roles and characteristics of ESP for STEM and the first step in introducing English for STEM vocabulary in STEM education. This paper implied that knowing the vocabulary for STEM could ensure better teaching and learning opportunities. Future research could look into designing and developing courses for English for STEM to leverage quality education as aspired in SDG.